2017
DOI: 10.3341/kjo.2016.0021
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Angle Kappa Using Ultrasound Biomicroscopy and Corneal Topography

Abstract: PurposeTo introduce a new convenient and accurate method to measure the angle kappa using ultrasound biomicroscopy (UBM) and corneal topography.MethodsData from 42 eyes (13 males and 29 females) were analyzed in this study. The angle kappa was measured using Orbscan II and calculated with UBM and corneal topography. The angle kappa of the dominant eye was compared with measurements by Orbscan II.ResultsThe mean patient age was 36.4 ± 13.8 years. The average angle kappa measured by Orbscan II was 3.98° ± 1.12°,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 15 publications
1
23
0
Order By: Relevance
“…In addition, a report designed a new method using UBM and corneal topography to calculate the angle kappa and compared the new method with Orbscan II, which found good correlations and agreement between the two methods. But there was statistically signi cant difference in angle kappa measured by the devices [2]. One explanation for the discrepancy between measurements might be the different principles in different devices, producing slightly different results.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In addition, a report designed a new method using UBM and corneal topography to calculate the angle kappa and compared the new method with Orbscan II, which found good correlations and agreement between the two methods. But there was statistically signi cant difference in angle kappa measured by the devices [2]. One explanation for the discrepancy between measurements might be the different principles in different devices, producing slightly different results.…”
Section: Discussionmentioning
confidence: 84%
“…Also, angle kappa can be classi ed as horizontal or vertical direction on the basis of X and Y Cartesian values of angle kappa. A positive angle kappa of average 5.0° is generally found in normal human eye [2].…”
mentioning
confidence: 93%
“…London and Wick reported a mean angle kappa of 5.08° . Yeo et al reported mean angle kappa as 3.98° ± 1.12° . The results may vary according to age, race and the patient's refractive status.…”
Section: Discussionmentioning
confidence: 99%
“…They also revealed a significant correlation between positive refractive errors and large positive angle kappa values which indicates that hyperopic patients have a larger angle kappa when compared to emmetropes and myopes . Yeo et al used ultrasound biomicroscopy and corneal topography to measure angle kappa and their results showed good reliability . Newer devices are available such as Galilei (Ziemer Ophthalmic Systems), and OPD Scan II (Nidek) to evaluate angle kappa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation